Manajemen Pemasaran Jasa Pendidikan di Era Digital: Analisis Strategi 7P pada MTs Al-Mursyidiyyah - Nurul Abidatul Muthayyibah; Safira Maulidiya; Intan Wiena Cahyaningrum; Nasirin Roset; Asti Cahya; Zahrotul Munawwaroh (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study aims to analyze educational marketing management strategies in attracting students’ interest at MTs Al-Mursyidiyyah. The research employed a qualitative approach using a descriptive-analytical method. Data were collected through literature review and in-depth interviews with the school principal as the key informant. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that MTs Al-Mursyidiyyah has comprehensively implemented educational marketing strategies based on the 7P marketing mix (product, price, place, promotion, people, physical evidence, and process). The product dimension is reflected in the integration of academic-religious curriculum supported by technology and diverse extracurricular programs. Promotional strategies are carried out through digital platforms such as Instagram, TikTok, and online admission websites, as well as conventional promotion through the annual November Festival. Strengthening human resources, modernizing facilities, and digitizing educational services also contribute to enhancing the school’s image. The study concludes that the success in attracting prospective students is strongly influenced by the synergy between product quality, promotional effectiveness, and physical evidence that build public trust in the educational institution.